The Creative Individual - Scott, William E. (Academy of Management Journal, 1965)
Observers of the American management scene have pointed to the recent interest in creativity as one of the more significant developments of our time. Behavioral scientists have also noted an upsurge of interests in creativity, pointing out that systematic investigations of the problem are of very recent origin. It is highly probable that in both cases the construct rather than the phenomena to which it refers has changed. One could, without difficulty, support the contention that managers have always been interested in what is now labeled creativity, and studies of eminent men and women were being reported in the 1920's and earlier. Apparently, however, the early studies were too crude and too limited in number to dispatch many of the common-sense myths surrounding creativity and the creative individual. Be that as it may, there is little question that the renewed interest has resulted in a greater number of studies involving more elegant experimental designs. Whereas controversy, speculation, and mythical beliefs characterized our knowledge about creativity prior to 1950, knowledge based upon empirical observations is beginning to take form. It would, of course, be a gross error to assume that the answers are all in. The results of some studies are clearly contradictory. Some studies represent nothing more than uncontrolled observations of a limited number of subjects so that one must necessarily question the reliability and generality of the findings. On the other hand, some results have consistently been found across studies incorporating reasonably good experimental designs. The purpose of this article is to review the progress that has been made on the assumption that it will help those faced with the responsibility of identifying and fostering creative talent in formal organizations as well as stimulate the development and testing of hypotheses which such a review inevitably suggests.